The Role of Tourism in Creating Employment in Khorasan Razavi Province - Hadi Rafiei Darani; Javad Barati (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2015)
Investment is a highly important economic variable that its increase or decrease can be a main cause of boom or recession in different economic sectors. It is also considered one of the most fundamental push factors in developing economic sectors. Tourism industry has a big share in Khorasan Razavi Province’s revenues. This papers aims to evaluate the impacts of tourism invesment on employment levels. In doing so, the study made use of an updated input – output (IO) table of Khorasan Razavi Province, and RAS method to develop and update the IO table. Results demonstrate that a one percent increase in the tourism investment (in Hotels and Restaurants), generates as many as 15,316 employment opportunites in the overal economy of the province, out of which 534 jobs are directly in tourism sector (equivalent to 3.5 % of total employment). The employment resulted from a one percent increase in the value-added of tourism, reflects a 58 percent share of employment in tourism sector and 42 percent in other activities.